Global situation for poliomyelitis. Who strategy and tactics of global polio eradication - M. A. Bichurina; N. I. Romanenkova; N. R. Rozaeva; V. A. Vorotnikova (Журнал инфектологии)
The review deals with the epidemic situation for poliomyelitis in the world. It describes the strategy and tactics of the World Health Organisation aimed at realisation of Global Polio Eradication Initiative and the main phases of the Initiative. The review shows the dynamics of poliomyelitis incidence over the years in the world and in different WHO regions. The events connected with the importation of wild poliovirus of type 1 to the countries of the WHO European region (Tajikistan, Turkmenistan, Kazakhstan and Russian Federation) which had been previously certified as polio free countries are treated in detail. The review also includes the data concerning the outbreaks of acute flaccid paralysis provoked by the circulating vaccine-derived polioviruses in certain countries. These events cause serious problems on the way of Global Polio eradication.